Pengembangan Tepung Ubi Jalar Ungu Pregelatinisasi serta Aplikasinya pada Pembuatan Flakes - Bryan, Bryan; Puspawati, Gusti Ayu Kadek Diah; Putra, I Nengah Kencana (Jurnal Ilmiah Teknologi Pertanian Agrotechno; Vol 9 No 2 (2024)DO - 10.24843/JITPA/2024.v09.i02.p01, 2025)
Purple sweet potato has good prospects as a raw material in the food industry, especially in the form of flour. However, purple sweet potato flour has several weaknesses such as low solubility in water, low water absorption capacity and the gel form is less uniform. The modification of purple cassava flour with pregelanitisation has been developed, but there is a decrease in the level of active components of anthocyanin and its antioxidants. The aim of this research is to find out the right pregelatinization temperature and time to produce the best modified purple sweet potato flour and to find out the ratio of modified purple sweet potato flour and moringa leaf flour to produce flakes with the best characteristics. This research was divided into two stages. The first stage was that the purple sweet potato was pregelatinized with a steaming temperature of 70 o C, 80 o C and 90 o C and steaming time of 5 minutes, 10 minutes and 15 minutes. The best results from the first stage of research were then applied to the second stage of research, namely the effect of adding Moringa leaf flour to purple sweet potato flakes with several levels, namely 0%, 3%, 6%, 9% and 12%. The results of the first stage of research showed that steaming treatment with a temperature of 70 o C and a duration of 5 minutes produced the best modified purple sweet potato flour with yield characteristics of 24.90%, anthocyanin content of 25,65 mg/L, starch content of 63.10%, amylose content of 28.73%, amylopectin content of 34.37%, anthocyanin content 25.62 mg/L, viscosity 2597 cP, water absorption capacity 113.27% and oil absorption capacity 110.68%. Modified purple sweet potato flour with the best treatment is used in making purple sweet potato flakes which is added with flour Moringa leaves. The treatment with the addition of 12% moringa leaf flour produced the best purple sweet potato flakes with yield characteristics of 59.41%, anthocyanin content of 8,02 mg/L, antioxidant activity of 19.31%, and organoleptic tests with characteristics of aroma is liked, slightly bitter and like taste, slightly crunchy and liked texture and the panelists overall acceptance is liked.